Molecular sieve and gamma-alumina blended composite carrier and preparation method thereof
Patent Information
- Application Number
- CN202611054160.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-13
AI Technical Summary
[0005]本发明的目的在于提供一种分子筛与γ-氧化铝共混复合载体及其制备方法与应用,以解决现有技术中分子筛与氧化铝界面结合强度弱、孔结构匹配性差、协同效应利用率低的技术问题
[0013]通过硅烷偶联剂对分子筛表面进行功能化预处理,再与铝溶胶进行原位凝胶化反应,在分子筛与γ-氧化铝之间构建了硅铝原子比呈梯度分布的界面过渡层,并形成硅氧铝化学键合,大幅度提升了界面结合强度,这是区别于现有物理混合法和简单共沉淀法的核心技术特征。
Smart Images

Figure CN122895031A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst support material technology, specifically relating to a molecular sieve and γ-alumina blended composite support and its preparation method. Background Technology
[0002] Molecular sieves and activated alumina are two of the most widely used catalyst support materials in the chemical industry. Activated alumina possesses abundant mesoporous structures, good thermal stability, and mechanical strength, with a specific surface area typically ranging from 150 to 350 square meters per gram and a total pore volume of 0.3 to 0.8 cubic centimeters per gram. However, its surface acidity is relatively weak, and its function is limited. Molecular sieves, on the other hand, have regular microporous structures, tunable acidity, and excellent shape selectivity. However, their mechanical strength is relatively low; the crushing strength of pure molecular sieves after molding is typically only 20 to 60 Newtons per centimeter. Under high-temperature hydrothermal conditions, they are prone to framework dealuminization and deactivation.
[0003] In practical industrial applications, activated alumina and molecular sieves are often used synergistically through alternating filling and segmented loading. While this tandem approach utilizes the advantages of both materials, it is essentially a physical combination of two independent materials, leading to issues such as mass transfer resistance and mismatched thermal expansion coefficients at the interface. Existing technologies also include methods that physically and mechanically mix molecular sieves and alumina before extrusion molding, and others that incorporate a mixture of molecular sieves and organic amines during the gelation process of amorphous alumina. However, in these methods, the interfacial bonding between the molecular sieve and alumina is mainly based on physical adsorption and simple mechanical interlocking, lacking chemical bonding-level interfacial reinforcement. This results in phase separation and gradual performance degradation during long-term high-temperature regeneration.
[0004] Based on the analysis of existing technologies, current molecular sieve-alumina composite carriers mainly suffer from the following problems: insufficient interfacial bonding strength; the contact between molecular sieve crystals and the alumina matrix is primarily physical, lacking chemical bonding, making them prone to phase separation after long-term repeated thermal cycling, leading to structural damage and performance degradation; poor pore structure matching; while molecular sieves provide micropores and alumina provides mesopores, the connectivity and gradient distribution between the two are not effectively controlled, resulting in poor micropore-mesopore mass transfer channels; low utilization rate of synergistic effect; in traditional mechanical mixing methods, a large number of molecular sieves are embedded inside the alumina matrix and cannot contact the reactants, resulting in low utilization rate of effective active sites; and difficulty in simultaneously achieving mechanical strength and specific surface area. Increasing the molecular sieve content can increase the specific surface area and the number of active sites, but it leads to a significant decrease in molding strength. Increasing the alumina content can improve strength, but it dilutes the concentration of active sites. Therefore, there is an urgent need to develop a novel composite carrier material that can overcome the above defects and achieve true synergistic effects between molecular sieves and γ-alumina. Summary of the Invention
[0005] The purpose of this invention is to provide a molecular sieve-γ-alumina blended composite support, its preparation method, and its application, to solve the technical problems of weak interfacial bonding strength, poor pore structure matching, and low utilization rate of synergistic effects between molecular sieves and alumina in the prior art. By constructing a composite support with a gradient interfacial coupling structure, uniform dispersion and chemical bonding of molecular sieves and γ-alumina at the nanoscale are achieved, thereby obtaining a novel support material with high specific surface area, rich hierarchical pore structure, and high mechanical strength.
[0006] To achieve the aforementioned objectives, this invention provides a molecular sieve and γ-alumina blended composite support, the core innovation of which lies in its gradient interface coupling structure. The composite support simultaneously possesses a three-tiered pore system comprising 0.4 to 1.2 nanometer micropores, 3 to 15 nanometer mesopores, and 50 to 500 nanometer macropores, with each pore level interconnected. A silicon-alumina transition layer with a thickness of 2 to 20 nanometers is formed between the molecular sieve particles and the γ-alumina matrix. In this transition layer, the silicon-to-alumina atomic ratio decreases in a gradient from the high silicon content on the molecular sieve surface to the high aluminum content on the alumina side, and silicon-alumina chemical bonds are formed within the transition layer. Based on the total mass of the composite support, the molecular sieve accounts for 15% to 65% of the mass, and the γ-alumina accounts for 35% to 85% of the mass. The composite carrier has a specific surface area of 280 to 550 square meters per gram, a total pore volume of 0.40 to 0.85 cubic centimeters per gram, a crushing strength of 80 to 200 Newtons per centimeter, and a specific surface area retention rate of not less than 85% after hydrothermal treatment at 650 degrees Celsius for 4 hours.
[0007] The present invention also provides a method for preparing the molecular sieve and γ-alumina blended composite support, comprising the following steps:
[0008] Step 1: Surface pretreatment of the molecular sieve. The raw molecular sieve powder is placed in an anhydrous ethanol solution containing a silane coupling agent, selected from at least one of γ-aminopropyltriethoxysilane, propyltrimethoxysilane, or γ-methacryloyloxypropyltrimethoxysilane. The amount of silane coupling agent is 0.5% to 5% of the molecular sieve mass. The mixture is stirred and refluxed at 50 to 78 degrees Celsius for 2 to 8 hours. After filtration and washing with ethanol, it is dried at 80 to 120 degrees Celsius for 2 to 4 hours to obtain a surface-functionalized molecular sieve. The key role of this step is that the silane coupling agent introduces reactive organic functional groups onto the surface of the molecular sieve, providing anchor points for chemical bonding with the alumina sol in subsequent steps. This is the chemical basis for constructing the gradient interface coupling layer.
[0009] Step 2: In-situ construction of the gradient interface layer. The surface-functionalized molecular sieve obtained in Step 1 is dispersed in deionized water to prepare a suspension A with a solid content of 5% to 25%. Separately, boehmite is mixed with deionized water, and 2.0 mol / L dilute nitric acid is slowly added dropwise under stirring to induce gelation. The pH is controlled at 3.5 to 5.0, the gelation temperature at 60 to 90 degrees Celsius, and the gelation time at 1 to 4 hours to obtain alumina sol B, wherein the mass ratio of boehmite to deionized water is 1:3 to 1:10. Suspension A is slowly added dropwise to aluminum sol B at a rate of 1 to 10 mL per minute, while maintaining a stirring speed of 200 to 800 rpm during the addition. After the addition is complete, stirring continues for 0.5 to 2 hours. Then, a 1.5 mol / L dilute ammonia solution is added dropwise at a rate of 0.5 to 2.0 mL per minute to adjust the pH of the system to 6.0 to 8.0, allowing the aluminum sol to gradually gel and deposit a gradient aluminum layer on the molecular sieve surface. After aging for 2 to 8 hours, a molecular sieve-aluminum gel composite with a gradient interface layer is obtained. This step is the core innovation of the method of this invention. By controlling the degree of gelation and the gelation rate of the aluminum sol, aluminum species are gradually deposited on the surface of the functionalized molecular sieve in a controlled manner, forming a transition layer with a gradient distribution of silicon-aluminum atomic ratio. During this process, the organic functional groups introduced by the silane coupling agent undergo a condensation reaction with the aluminum hydroxyl groups in the aluminum sol to generate silicon-aluminum chemical bonds, thereby achieving chemical bonding at the interface.
[0010] Step 3, Molding and Calcination. The molecular sieve-aluminum gel composite obtained in Step 2 is mixed with a molding aid selected from at least one of guar gum powder, carboxymethyl cellulose, or polyethylene glycol. An appropriate amount of deionized water is added to adjust the moisture content of the material to 35% to 55%. After kneading and extrusion molding, the resulting molded material is allowed to air-dry at room temperature for 4 to 12 hours, then dried at 80 to 120 degrees Celsius for 4 to 12 hours. It is then calcined at 450 to 650 degrees Celsius for 3 to 8 hours at a heating rate of 1 to 5 degrees Celsius per minute to obtain the molecular sieve and γ-alumina blended composite carrier. During calcination, boehmite decomposes into γ-alumina, while the organic components in the silane coupling agent decompose and are removed, while silicon elements remain in the interfacial transition layer, ultimately forming a stable silica-alumina chemically bonded interface.
[0011] As a preferred technical solution, in step one, propyltrimethoxysilane is selected as the silane coupling agent, and its dosage is 2% of the molecular sieve mass. In step two, the solid content of suspension A is 15%, the pH value of the aluminum sol is 4.0, the gelation temperature is 75 degrees Celsius, the final pH value is adjusted to 7.0 by adding dilute ammonia, and the aging time is 4 hours. In step three, the calcination temperature is 550 degrees Celsius, and the calcination time is 5 hours.
[0012] Compared with the prior art, the innovation and beneficial effects of this invention are reflected in the following aspects:
[0013] By functionalizing the surface of the molecular sieve with a silane coupling agent and then performing an in-situ gelation reaction with aluminum sol, an interfacial transition layer with a gradient distribution of silicon-aluminum atomic ratio is constructed between the molecular sieve and γ-alumina, and a silicon-oxygen-aluminum chemical bond is formed, which greatly improves the interfacial bonding strength. This is the core technical feature that distinguishes it from the existing physical mixing method and simple co-precipitation method.
[0014] By controlling the gelation conditions and gelation rate of aluminum sol, precise control of mesopore size in the range of 3 to 15 nanometers was achieved, and a three-level interconnected pore system was formed with molecular sieve micropores and interparticle stacked macropores, which takes into account both high specific surface area and excellent mass transfer efficiency.
[0015] The presence of the gradient interface coupling layer effectively transfers and disperses stress, enabling the composite carrier to achieve a crushing strength of 80 to 200 Newtons per centimeter. After hydrothermal treatment at 650 degrees Celsius for 4 hours, the specific surface area retention rate is not less than 85%, which is significantly better than the composite carrier prepared by the traditional mechanical mixing method.
[0016] By adjusting the type and content ratio of molecular sieves, the acidity, pore structure and surface properties of composite carriers can be flexibly controlled to meet the needs of various application scenarios such as carbon dioxide adsorption, VOCs catalytic oxidation and hydrodesulfurization. Attached Figure Description
[0017] Figure 1 This is a flowchart of the steps of the present invention. Detailed Implementation
[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0019] SM-5 molecular sieve raw powder: SiO2 / Al2O3 ratio = 50, specific surface area ≥ 350 m² 2 / g, purchased from Nankai University Catalyst Factory;
[0020] Y-type molecular sieve raw powder: SiO2 / Al2O3 ratio = 5.2, specific surface area ≥ 600 m² 2 / g, purchased from Nankai University Catalyst Factory;
[0021] 13X molecular sieve raw powder: SiO2 / Al2O3 ratio = 2.5, specific surface area ≥ 500 m² 2 / g, purchased from Shanghai Hengye Molecular Sieve Co., Ltd.;
[0022] Beta molecular sieve raw powder: SiO2 / Al2O3 ratio = 25, specific surface area ≥ 450 m² 2 / g, purchased from Nankai University Catalyst Factory;
[0023] SAPO-34 molecular sieve raw powder: specific surface area ≥400 m² 2 / g, homemade;
[0024] Boehmite: Al2O3 content ≥70%, specific surface area ≥250 m² 2 / g, purchased from Aluminum Corporation of China Limited;
[0025] KH-560 silane coupling agent: purity ≥97%, purchased from Nanjing Shuguang Chemical Group Co., Ltd.;
[0026] KH-550 silane coupling agent: purity ≥97%, purchased from Nanjing Shuguang Chemical Group Co., Ltd.;
[0027] Dilute nitric acid and dilute ammonia: analytical grade, purchased from Sinopharm Chemical Reagent Co., Ltd.
[0028] Guarbanum powder, carboxymethyl cellulose, polyethylene glycol: industrial grade;
[0029] Cobalt nitrate (Co(NO3)2·6H2O), ammonium molybdate ((NH4)6Mo7O) 24 ·4H2O), nickel nitrate (Ni(NO3)2·6H2O), chloroplatinic acid (H2PtCl6·6H2O).
[0030] Example 1
[0031] This embodiment provides a method for preparing a ZSM-5 and γ-alumina blended composite carrier.
[0032] Step 1: Take 100g of ZSM-5 molecular sieve raw powder with a silicon-to-aluminum ratio of 50, add it to 500ml of anhydrous ethanol solution containing 3g of propyltrimethoxysilane coupling agent, stir and reflux at 75°C for 4 hours, filter, wash 3 times with anhydrous ethanol, and dry at 100°C for 3 hours to obtain surface-functionalized ZSM-5 molecular sieve.
[0033] Step 2: Take 50 g of the above-mentioned functionalized ZSM-5 molecular sieve, disperse it in 280 mL of deionized water, and sonicate for 20 minutes to obtain suspension A with a solid content of approximately 15%. Separately, take 167 g of boehmite, add it to 500 mL of deionized water and stir evenly. Under stirring at 75°C, slowly add 1.5 mol / L dilute nitric acid for gelation, controlling the endpoint pH to 4.0, and continue stirring for 2 hours to obtain aluminum sol B. Slowly add suspension A to aluminum sol B at a rate of 3 mL / min, maintaining a stirring speed of 400 rpm during the addition. After the addition is complete, continue stirring for 1 hour. Then, add 1.0 mol / L dilute ammonia solution at a rate of 1.0 mL / min to adjust the pH of the system to 7.0, continue stirring for 30 minutes, and then allow it to stand for 4 hours to age, obtaining the ZSM-5 aluminum gel complex with a gradient interface layer.
[0034] Step 3: Mix the composite obtained in Step 2 with 3 grams of guar gum powder and 2 grams of carboxymethyl cellulose. Add an appropriate amount of deionized water to adjust the moisture content to about 45%. Knead in a kneader for 1 hour, then extrude into strips using a twin-screw extruder with a die aperture of 2.0 mm. After the strips are air-dried at room temperature for 8 hours, they are dried at 110 degrees Celsius for 8 hours, and then calcined at 550 degrees Celsius at a heating rate of 2 degrees Celsius per minute for 5 hours to obtain the ZSM-5 and γ-alumina blended composite carrier, denoted as CZ-1.
[0035] Characterization revealed that CZ-1 had a specific surface area of 385 m² / g, a total pore volume of 0.58 cm³ / g, a micropore volume of 0.09 cm³ / g, a mesopore volume of 3-15 nm of pore size of 0.38 cm³ / g, and a crushing strength of 135 N / cm. Transmission electron microscopy showed a transition layer of approximately 5-10 nm thickness surrounding the molecular sieve particles. Energy dispersive spectroscopy confirmed a gradient decreasing silicon-to-aluminum ratio in the transition layer, and the infrared spectrum showed a characteristic absorption peak of silicon-oxygen-aluminum at wavenumber 960.
[0036] Example 2
[0037] This embodiment provides a method for preparing a Y-type and γ-alumina blended composite carrier.
[0038] Step 1: Take 100g of Y-type molecular sieve raw powder with a silicon-to-aluminum ratio of 5.2, add it to 500ml of anhydrous ethanol solution containing 2.5g of propyltrimethoxysilane coupling agent, stir and reflux at 70°C for 5 hours, filter, wash 3 times with anhydrous ethanol, and dry at 110°C for 3 hours to obtain surface-functionalized Y-type molecular sieve.
[0039] Step 2: Take 70 g of functionalized Y-type molecular sieve and disperse it in 350 mL of deionized water. Sonicate the solution for 25 minutes to obtain suspension A with a solid content of approximately 16.7%. Separately, take 150 g of boehmite and add it to 450 mL of deionized water. While stirring at 80°C, add 1.5 mol / L dilute nitric acid dropwise to dissolve the gel until the pH reaches 4.2. Continue stirring for 2 hours to obtain aluminum sol B. Add suspension A dropwise to aluminum sol B at a rate of 4 mL / min, maintaining a stirring speed of 500 rpm. After the addition is complete, continue stirring for 1 hour. Adjust the pH to 6.8 by adding 1.0 mol / L dilute ammonia dropwise at a rate of 1.2 mL / min. Aging for 5 hours yields the Y-type aluminum gel complex.
[0040] Step 3: Mix the composite with 4 grams of guar gum powder, adjust the moisture content to 48%, knead and extrude into strips with a mold aperture of 2.0 mm, let it air dry at room temperature for 10 hours, dry at 110 degrees Celsius for 10 hours, and calcine at 580 degrees Celsius for 5 hours at a heating rate of 3 degrees Celsius per minute to obtain the Y-type and γ-alumina blended composite carrier, denoted as CZ-2.
[0041] Characterization showed that CZ-2 had a specific surface area of 460 square meters per gram, a total pore volume of 0.65 cubic centimeters per gram, a micropore volume of 0.14 cubic centimeters per gram, a mesopore volume of 0.42 cubic centimeters per gram, a crushing strength of 110 Newtons per centimeter, and a gradient interface layer thickness of approximately 10 nanometers.
[0042] Example 3
[0043] This embodiment provides a method for preparing a composite carrier of 13X and γ-alumina.
[0044] Step 1: Take 100g of 13X molecular sieve raw powder with a silicon-to-aluminum ratio of 2.5, add it to 500ml of anhydrous ethanol solution containing 2g of γ-aminopropyltriethoxysilane coupling agent, stir and reflux at 65°C for 6 hours, filter and wash, and dry at 100°C for 4 hours to obtain functionalized 13X molecular sieve.
[0045] Step 2: Take 90 g of functionalized 13X molecular sieve and disperse it in 450 mL of deionized water. Sonicate the solution for 30 minutes to obtain suspension A with a solid content of approximately 16.7%. Take 129 g of boehmite and add it to 400 mL of deionized water. Add 1.5 mol / L dilute nitric acid dropwise at 70°C until the pH reaches 4.5. Stir for 2 hours to obtain aluminum sol B. Add suspension A dropwise to aluminum sol B at a rate of 5 mL / min while stirring at 300 rpm. After the addition is complete, continue stirring for 1.5 hours. Adjust the pH to 7.2 by adding 1.0 mol / L dilute ammonia dropwise at a rate of 0.8 mL / min. Aging for 6 hours.
[0046] Step 3: Add 3 grams of guar gum powder and 3 grams of polyethylene glycol, adjust the moisture content to 50%, knead and extrude into strips with a mold aperture of 2.0 mm, let it air dry at room temperature for 12 hours, dry it at 105 degrees Celsius for 12 hours, and calcine it at 500 degrees Celsius for 6 hours with a heating rate of 2 degrees Celsius per minute to obtain the 13X and γ-alumina blended composite carrier, denoted as CZ-3.
[0047] Characterization showed that CZ-3 had a specific surface area of 510 square meters per gram, a total pore volume of 0.72 cubic centimeters per gram, a micropore volume of 0.18 cubic centimeters per gram, a crushing strength of 95 Newtons per centimeter, and a specific surface area retention rate of 89% after hydrothermal treatment at 650 degrees Celsius for 4 hours.
[0048] Example 4
[0049] This embodiment provides a method for preparing a composite carrier of Beta and γ-alumina.
[0050] Step 1: Take 100g of Beta molecular sieve raw powder with a silica-to-alumina ratio of 25, add it to 500ml of anhydrous ethanol solution containing 3.5g of γ-methacryloyloxypropyltrimethoxysilane coupling agent, stir and reflux at 78°C for 3 hours, filter and wash, and dry at 90°C for 4 hours to obtain functionalized Beta molecular sieve.
[0051] Step 2: Take 35 g of functionalized Beta molecular sieve, disperse it in 200 mL of deionized water, and sonicate for 20 minutes to obtain suspension A with a solid content of approximately 15%. Take 200 g of boehmite, add it to 550 mL of deionized water, and add 1.5 mol / L dilute nitric acid dropwise at 75°C to adjust the pH to 3.8. Stir for 2.5 hours to obtain aluminum sol B. Add suspension A dropwise to aluminum sol B at a rate of 2 mL / min, stirring at 600 rpm. After the addition is complete, stir for 1 hour, and then add 1.0 mol / L dilute ammonia dropwise at a rate of 1.5 mL / min to adjust the pH to 7.0. Aging is then carried out for 4 hours.
[0052] Step 3: Add 5 grams of guar gum powder, adjust the moisture content to 42%, knead and extrude into strips with a mold aperture of 2.5 mm, let it air dry at room temperature for 6 hours, dry it at 120 degrees Celsius for 6 hours, and calcine it at 600 degrees Celsius for 4 hours at a heating rate of 3 degrees Celsius per minute to obtain the Beta and γ-alumina blended composite carrier, denoted as CZ-4.
[0053] Characterization showed that CZ-4 has a specific surface area of 310 square meters per gram, a total pore volume of 0.52 cubic centimeters per gram, and a crushing strength of 165 Newtons per centimeter.
[0054] Example 5
[0055] This embodiment provides a method for preparing a ZSM-5 and γ-alumina blended composite carrier. The steps are the same as in Embodiment 1, except that in step 2, the amount of functionalized ZSM-5 molecular sieve is adjusted to 90 g and dispersed in 400 ml of deionized water, and the amount of boehmite is adjusted to 129 g. Other conditions remain unchanged, and the resulting product is denoted as CZ-5.
[0056] Characterization showed that CZ-5 had a specific surface area of 425 square meters per gram, a total pore volume of 0.63 cubic centimeters per gram, a micropore volume of 0.15 cubic centimeters per gram, and a crushing strength of 88 Newtons per centimeter.
[0057] Comparative Example 1
[0058] This comparative example uses a traditional mechanical mixing method to prepare a composite carrier. 50 g of ZSM-5 molecular sieve powder and 167 g of pseudoboehmite were directly mechanically mixed, 3 g of guar gum powder and an appropriate amount of deionized water were added, and the mixture was kneaded, extruded, dried at 110 degrees Celsius for 8 hours and calcined at 550 degrees Celsius for 5 hours to obtain a traditional mechanically mixed carrier, denoted as DZ-1.
[0059] Characterization revealed that DZ-1 had a specific surface area of 340 m² / g, a total pore volume of 0.50 cm³ / g, and a crushing strength of 62 N / cm. Transmission electron microscopy showed a clear interface between the molecular sieve and alumina, with obvious gaps, and no characteristic absorption peaks of aluminosilicate were detected in the infrared spectrum. After hydrothermal treatment at 650°C for 4 hours, the specific surface area decreased to 225 m² / g, with a retention rate of only 66%.
[0060] Comparative Example 2
[0061] This comparative example omits the surface functionalization treatment step, and other conditions are the same as in Example 1. The ZSM-5 molecular sieve raw powder is used directly in the preparation of the suspension in step two without being treated with propyltrimethoxysilane, and the resulting carrier is denoted as DZ-2.
[0062] Characterization revealed that DZ-2 had a specific surface area of 360 m² / g, a total pore volume of 0.53 cm³ / g, and a crushing strength of 78 N / cm. Transmission electron microscopy showed alumina deposition on the molecular sieve surface, but the interfacial transition layer thickness was uneven, and the silica-alumina absorption peak in the infrared spectrum was weak. After hydrothermal treatment at 650°C for 4 hours, the specific surface area retention rate was 73%.
[0063] Comparative Example 3
[0064] This comparative example was prepared using a rapid gelation method, with step one being the same as in Example 1. In step two, after adding suspension A, concentrated ammonia was added rapidly in one go to instantly raise the pH of the system to above 8.5, causing the aluminum sol to gel rapidly. The other steps were the same as in Example 1, and the resulting carrier was designated as DZ-3.
[0065] Characterization revealed that DZ-3 has a specific surface area of 370 m² / g, a total pore volume of 0.55 cm³ / g, and a crushing strength of 72 N / cm. Transmission electron microscopy showed that the molecular sieve surface had only an uneven alumina deposit, with no gradient transition layer structure observed. Energy dispersive spectroscopy (EDS) indicated that the silicon-to-aluminum ratio exhibited an abrupt change rather than a gradient at the interface.
[0066] Comparative Example 4
[0067] This comparative example uses only boehmite as raw material to prepare pure γ-alumina support. Boehmite was dissolved in dilute nitric acid until the pH reached 4.0. The dissolution temperature was 75°C, and the dissolution time was 2 hours. 3 grams of guar gum powder were added, and the mixture was kneaded, extruded, dried at 110°C, and calcined at 550°C for 5 hours to obtain pure γ-alumina support, denoted as DZ-4.
[0068] Characterization showed that DZ-4 has a specific surface area of 245 square meters per gram, a total pore volume of 0.45 cubic centimeters per gram, and a crushing strength of 145 Newtons per centimeter.
[0069] Summary of performance of each embodiment and comparative example
[0070] The following table summarizes the main physicochemical properties of each embodiment (CZ-1 to CZ-5) and comparative examples (DZ-1 to DZ-4):
[0071]
[0072] As can be seen from the table, the composite carrier prepared in the embodiments of the present invention is significantly superior to each comparative example in terms of specific surface area and crushing strength, and has excellent hydrothermal stability.
[0073] Most importantly, the embodiment achieves a high specific surface area while maintaining high mechanical strength (CZ-1: 385m). 2 / g, 135 N / cm, while the comparative example DZ-1 prepared by the traditional method, although having a decent specific surface area, has a crushing strength of only 62 N / cm, which is far below the requirements for industrial use.
[0074] Application Examples
[0075] Application Example A: Evaluation of CO2 Adsorption Performance
[0076] The carriers of Examples 1, 3, 1, 2, 3, and 4 were crushed and sieved into 20-40 mesh particles, and then vacuum degassed at 200°C for 3 h. The CO2 adsorption isotherm was tested at 25°C using the static volumetric method.
[0077] Test conditions: adsorption temperature 25℃, CO2 partial pressure range 0~100 kPa, sample mass approximately 1.0 g.
[0078] Test results: At a CO2 partial pressure of 100 kPa, the CO2 adsorption capacity of CZ-1 was 2.85 mmol / g, CZ-3 was 4.12 mmol / g, DZ-1 was 2.10 mmol / g, DZ-2 was 2.28 mmol / g, DZ-3 was 2.19 mmol / g, and DZ-4 was 1.35 mmol / g. The adsorption capacity of CZ-3 was significantly higher than all comparative samples. It is noteworthy that although the CO2 adsorption capacities of DZ-2 and DZ-3 were slightly higher than those of DZ-1, they were still much lower than those of CZ-1. This indicates that without silane coupling agent functionalization, an effective gradient interface coupling structure cannot be formed, the accessibility of the molecular sieve micropores is poor, and a large number of molecular sieve particles are embedded in the alumina matrix and cannot effectively participate in CO2 adsorption. After 10 adsorption-desorption cycles, the CO2 adsorption capacity retention rate of CZ-3 was 96.5%, that of DZ-1 was 82.3%, that of DZ-2 was 85.1%, and that of DZ-3 was 83.7%, indicating that the gradient interface coupling structure effectively suppressed phase separation and performance degradation caused by repeated thermal cycling.
[0079] Application Example B: Evaluation of VOCs Catalytic Oxidation Performance
[0080] Using CZ-1, DZ-1, and DZ-4 as supports, 1.0 wt% Pt was loaded onto the catalysts using the equal-volume impregnation method to prepare catalysts containing Pt on CZ-1, DZ-1, and DZ-4 supports, respectively.
[0081] Impregnation method: Take 10 g of each carrier, calculate the required amount of H2PtCl6·6H2O based on a Pt loading of 1.0 wt%, dissolve it in an appropriate amount of deionized water to prepare an impregnation solution, impregnate the carrier with an equal volume, let stand at room temperature for 4 h, dry at 110℃ for 6 h, and calcine at 450℃ for 3 h.
[0082] Catalytic activity evaluation conditions: fixed-bed reactor, toluene concentration 1000 ppm, liquid hourly space velocity (LHSV) = 2 h⁻¹ -1 The reaction temperature is 150–350℃.
[0083] Evaluation results: The temperature T50 for achieving 50% toluene conversion on the Pt-containing CZ-1 supported catalyst was 195℃, and the temperature T90 for achieving 90% conversion was 228℃; the temperature T50 for the Pt-containing DZ-1 supported catalyst was 228℃, and the temperature T90 was 275℃.
[0084] The T50 of the Pt-containing DZ-4 supported catalyst is 210℃, and the T90 is 268℃. The catalytic activity of the Pt-containing CZ-1 supported catalyst is significantly better than that of the Pt-containing DZ-1 and Pt-containing DZ-4 supported catalysts. The complete conversion temperature is about 47℃ lower than that of the Pt-containing DZ-1 supported catalyst and about 40℃ lower than that of the Pt-containing DZ-4 supported catalyst.
[0085] Although the pure γ-Al2O3 support loaded with Pt exhibits certain toluene oxidation activity, its T50 and T90 are both higher than those of the Pt-containing CZ-1 support, indicating that the introduction of molecular sieves and their gradient interface coupling structure with alumina have a positive effect on improving the catalytic oxidation activity of Pt.
[0086] To further clarify the source of the improved catalytic performance, the dispersion of Pt was determined by CO chemisorption and the particle size of Pt was determined by high-resolution transmission electron microscopy (HRTEM).
[0087] Characterization results showed that the Pt dispersion on the CZ-1 support containing Pt was 38.5%, with an average particle size of 2.8 nm; the Pt dispersion on the DZ-1 support containing Pt was 22.3%, with an average particle size of 4.5 nm; and the Pt dispersion on the DZ-4 support containing Pt was 25.6%, with an average particle size of 3.9 nm.
[0088] The Pt dispersion on the Pt-containing CZ-1 support was significantly higher than that of the two comparative samples, and the particle size was also smaller. This indicates that the hierarchical porous system and abundant surface anchoring points provided by the gradient interface coupling structure are conducive to the uniform dispersion and confined growth of the Pt precursor, thereby inhibiting the sintering and growth of Pt particles during calcination. Therefore, the excellent catalytic performance of the Pt-containing CZ-1 support is attributed to the combined contribution of the support's pore structure advantage and the improved Pt metal dispersion state.
[0089] Furthermore, in the stability test conducted after 100 hours of continuous operation at 250°C, the toluene conversion rate on the Pt-containing CZ-1 support decreased from the initial 94.5% to 91.8%, with an activity retention rate of 97%; the Pt-containing DZ-1 support decreased from 88.2% to 78.5%, with a retention rate of only 89%; and the Pt-containing DZ-4 support decreased from 91.0% to 82.3%, with a retention rate of 90.4%. The Pt-containing CZ-1 support catalyst exhibited the best thermal stability and anti-sintering ability.
[0090] Evaluation of hydrodesulfurization performance using Example C:
[0091] Using CZ-2, DZ-1, and DZ-4 as supports, Co and Mo active components were loaded using an equal-volume impregnation method, wherein CoO was 4.0 wt% and MoO3 was 15.0 wt%, respectively, to prepare catalysts containing Co and Mo on the CZ-2 support, the DZ-1 support, and the DZ-4 support.
[0092] Impregnation method: Dissolve cobalt nitrate and ammonium molybdate in an appropriate amount of deionized water according to the required CoO and MoO3 loading, impregnate with equal volumes, let stand at room temperature for 6 h, dry at 110℃ for 8 h, and calcine at 500℃ for 4 h. Before use, pre-vulcanize at 400℃ with H2 containing 10 vol% H2S for 2 h.
[0093] Activity evaluation conditions: Fixed-bed high-pressure reactor; model compound: n-heptane solution containing 0.5 wt% dibenzothiophene (DBT); reaction temperature: 300℃; pressure: 3.0 MPa; hydrogen-to-oil volume ratio: 300; liquid hourly space velocity (LHSV): 2.0 h⁻¹. -1 .
[0094] Evaluation results: At 320℃, the DBT removal rate on the CZ-2 supported catalyst containing Co and Mo was 98.2%, the DBT removal rate on the DZ-1 supported catalyst containing Co and Mo was 88.5%, and the DBT removal rate on the DZ-4 supported catalyst containing Co and Mo was 85.7%. CZ-2 contains 40% Y-type molecular sieve, and its number and type of acidic sites are fundamentally different from those of the pure γ-Al₂O₃ supported catalyst DZ-4. By introducing DZ-1 as a comparison, it can be seen that although DZ-1 also contains ZSM-5 molecular sieve, its DBT removal rate of 88.5% is still significantly lower than that of CZ-2 (98.2%). This indicates that the improvement in hydrodesulfurization performance by the gradient interface coupling structure not only comes from the contribution of the acidic sites of the molecular sieve, but also benefits from the high accessibility of the acidic sites ensured by the gradient interface coupling layer and the diffusion and mass transfer of reactant molecules promoted by the interconnected multi-level pore system. Although the DZ-4 support containing Co and Mo does not contain molecular sieves, it exhibits the lowest DBT removal rate, further confirming the important role of acidic sites in the hydrodesulfurization reaction. The CZ-2 support catalyst containing Co and Mo demonstrates the best hydrodesulfurization activity because the Y-type molecular sieve provides abundant Brønsted and Lewis acid sites, promoting the breaking of CS bonds in DBT. Simultaneously, the gradient interfacial coupling structure enhances the synergistic effect between the active metal and the support.
[0095] Application Example D: Performance Evaluation of CO2 Catalytic Hydrogenation to Methanol
[0096] Using CZ-3, DZ-1, and DZ-2 as supports, Cu-Zn active components were loaded using a deposition-precipitation method, wherein Cu was 30 wt% and Zn was 10 wt%, to prepare catalysts containing Cu and Zn on the CZ-3 support, the DZ-1 support, and the DZ-2 support.
[0097] Preparation method: Take 10 g of the carrier, dissolve the required amounts of copper nitrate and zinc nitrate in 200 mL of deionized water, add the carrier, stir and heat to 70℃, add 1.0 mol / L Na2CO3 solution dropwise to adjust the pH to 8.0, stir and age for 3 h, filter and wash, dry at 110℃ for 8 h, and calcine at 350℃ for 3 h. Before use, reduce with N2 containing 5 vol% H2 at 250℃ for 3 h.
[0098] Activity evaluation conditions: fixed-bed reactor, feed gas ratio of H2 / CO2 = 3:1, reaction temperature 250℃, pressure 4.0MPa, LHSV = 3 h-1.
[0099] Evaluation results: At 250℃, the CO2 conversion rate on the CZ-3 supported catalyst containing Cu and Zn was 18.5%, the methanol selectivity was 72.3%, and the methanol space-time yield was 0.42 g·g-1·h-1.
[0100] The CO2 conversion on the DZ-1 supported catalyst containing Cu and Zn was 15.2%, the methanol selectivity was 67.5%, and the space-time yield was 0.32 g·g⁻¹·h⁻¹. The CO2 conversion on the DZ-2 supported catalyst containing Cu and Zn was 13.8%, the methanol selectivity was 63.1%, and the space-time yield was 0.27 g·g⁻¹·h⁻¹. The catalytic performance of the CZ-3 supported catalyst containing Cu and Zn was significantly better than that of DZ-1 and DZ-2.
[0101] DZ-1, a mechanically mixed support, exhibited lower CO2 conversion and methanol selectivity than CZ-3. This indicates that the gradient interface coupling structure, by constructing a Si-O-Al chemically bonded interface, enhances the support's affinity for CO2 adsorption, promoting CO2 enrichment near the active sites and thus improving conversion and methanol selectivity. Although DZ-2 underwent chemical deposition, it lacked silane coupling agent functionalization, resulting in weaker interfacial bonding than CZ-3, and its catalytic performance was also inferior. This comparative sequence clearly demonstrates the unique contribution of the gradient interface coupling structure to the CO2 hydrogenation to methanol reaction.
[0102] Application Example E: Evaluation of MTO Reactivity of SAPO-34 / γ-Al2O3 Blend Support
[0103] Preparation of support and catalyst: 100 g of SAPO-34 molecular sieve powder was surface-functionalized with KH-560 according to step 1 of Example 1. 60 g of the functionalized SAPO-34 molecular sieve was then mixed with 130 g of boehmite according to steps 2 and 3 of Example 1 to construct a gradient interface layer and extrude the mixture. The calcination temperature was adjusted to 600℃ to obtain SAPO-34 / γ-A. l2 O3-blended composite carrier CZ-6. CZ-6 has a specific surface area of 420 m². 2 / g, total pore volume is 0.56 cm³ 3 / g, crushing strength is 105 N / cm.
[0104] In comparison, a support, designated DZ-5, was prepared by mechanical mixing of SAPO-34 molecular sieve and pseudoboehmite in the same proportions, with a specific surface area of 375 m². 2 / g, crushing strength is 55 N / cm.
[0105] The reasons for adjusting the calcination temperature of CZ-6 to 600℃ are as follows: The thermal stability of the SAPO-34 molecular sieve framework is slightly lower than that of the silicon-aluminum molecular sieve. Excessively high calcination temperatures may lead to irreversible structural damage to the SAPO-34 framework and phase separation of phosphorus-aluminum species, while excessively low temperatures are insufficient to completely convert boehmite into γ-Al₂O₃. Through systematic experimental optimization, 600℃ can achieve sufficient crystallization of boehmite while ensuring the structural integrity of SAPO-34, while simultaneously ensuring the complete removal of organic components from the silane coupling agent and the full formation of the Si-O-Al chemical bonding interface.
[0106] TEM and EDS line scans were used to characterize DZ-5 to reveal its interface structure differences from CZ-6: TEM images showed a clear interfacial gap between the SAPO-34 molecular sieve particles and the alumina matrix in DZ-5, with a width of approximately 8–20 nm. The two phases were clearly defined and physically separated. No interfacial transition layer structure was observed in high-resolution images. EDS line scan analysis showed a step-like abrupt change in the silicon-to-alumina atomic ratio at the interface, transitioning directly from the high silicon content on the molecular sieve side to the low silicon content on the alumina side, without any gradient transition characteristics. FTIR spectroscopy did not detect the characteristic Si-O-Al absorption peak at 960 cm⁻¹ in DZ-5, confirming that the molecular sieve and alumina are only in physical contact and lack chemical bonding. These characterization data contrast sharply with the gradient interfacial coupling structure of CZ-6.
[0107] Activity evaluation conditions: fixed-bed reactor, raw material is pure methanol, reaction temperature is 450℃, methanol mass hourly space velocity (WHSV) is 2.0 h⁻¹, atmospheric pressure, N₂ carrier gas flow rate is 30 mL / min.
[0108] Evaluation results: The CZ-6 catalyst achieved a methanol conversion of 99.5% and a total ethylene + propylene selectivity of 83.2%, which remained at 80.1% after 100 hours of operation. The DZ-5 catalyst initially achieved a conversion of 98.8% and a total ethylene + propylene selectivity of 78.5%, but the selectivity rapidly decreased to 68.3% after 100 hours of operation. CZ-6 demonstrated significant advantages in both olefin selectivity and operational stability.
[0109] To further elucidate the reasons for the rapid deactivation of DZ-5, thermogravimetric analysis (TGA) and N2 adsorption-desorption characterization were performed on the DZ-5 catalyst after 100 h of reaction. TGA results showed that DZ-5 experienced a 12.8 wt% weight loss due to carbonization in air, while CZ-6 only experienced a 6.5 wt% loss, indicating that the carbon deposition on DZ-5 was significantly higher than that on CZ-6. N2 adsorption-desorption results showed that the specific surface area of DZ-5 increased from 375 m² / s² after the reaction. 2 / g decreased to 215 m 2 / g, a decrease of 42.7%, with particularly severe loss in micropore volume, from 0.16 cm 3 / g decreased to 0.07cm 3 / g; while the specific surface area of CZ-6 after the reaction increased from 420 m² / g; 2 / g decreased to 355 m 2 / g, a decrease of only 15.5%. These results indicate that the rapid deactivation of DZ-5 is mainly due to two reasons: firstly, the weak interfacial bonding between the molecular sieve and alumina in the support prepared by the mechanical mixing method makes the two phases prone to microscopic separation during the reaction, leading to structural damage and pore blockage; secondly, the lack of a through-hole mesoporous mass transfer channel provided by the gradient interface coupling layer causes the olefin products generated in the MTO reaction to remain in the microporous cages of the SAPO-34 molecular sieve for too long, further transforming into carbon precursors and ultimately depositing as carbon species, blocking the microporous channels of the molecular sieve and leading to rapid catalyst deactivation. In contrast, the mesoporous channels provided by the gradient interface coupling layer in CZ-6 facilitate the rapid diffusion and desorption of reaction products, inhibiting the secondary reaction of olefins further transforming into carbon precursors within the SAPO-34 molecular sieve cages, thereby significantly extending the catalyst lifetime.
[0110] Comparative analysis of proportional systems
[0111] Interface structure comparison
[0112] Comparative analysis of Example 1 and Comparative Examples 1-3 using TEM and EDS line scans:
[0113] CZ-1: TEM images show that the interface between the molecular sieve particles and the alumina matrix is continuous and without obvious cracks. High-resolution images show an interface transition layer with a thickness of 5-10 nm. EDS line scans show that the silicon-aluminum atomic ratio in the interface transition layer decreases smoothly from ≈25 on the molecular sieve side to ≈0.05 on the alumina side, confirming the existence of the gradient interface coupling layer.
[0114] DZ-1: TEM images show a clear interfacial gap of about 5-15 nm between the molecular sieve and alumina. EDS line scans show a step-like abrupt change in the silicon-aluminum atomic ratio at the interface, indicating that the two are only in physical contact and have no chemical bonding.
[0115] DZ-2: TEM showed alumina deposition on the surface of the molecular sieve, but the thickness of the interfacial transition layer was uneven, ranging from 0 to 6 nm. EDS line scanning showed that although the ratio of silicon to aluminum atoms showed a transitional trend, it fluctuated irregularly and did not form an ideal gradient structure. This indicates that the surface of the molecular sieve without silane coupling agent functionalization lacks anchor points for effective bonding with aluminum species.
[0116] DZ-3: TEM showed that only alumina agglomerates of varying thicknesses were attached to the surface of the molecular sieve. EDS line scan showed that the ratio of silicon to aluminum atoms changed abruptly at the interface, without gradient transition characteristics. This is because rapid gelation caused a large amount of aluminum species to be deposited instantaneously on the surface of the molecular sieve, making it impossible to achieve an ordered gradient arrangement.
[0117] Hole structure comparison
[0118] The pore structures of CZ-1, DZ-1, and DZ-4 were systematically compared using N2 adsorption-desorption and mercury porosimetry.
[0119] CZ-1 exhibits three clear mesoporous peaks at 3.8 nm, 7.2 nm, and 12.5 nm in the BJH mesoporous pore size distribution, indicating that the gradient gelation method effectively regulates the multi-level distribution of mesopores; the microporous region shows obvious molecular sieve microporous characteristics; mercury porosimetry shows that there are interparticle-accumulated macropores in the range of 50–300 nm.
[0120] The mesopore distribution of DZ-1 is mainly concentrated at 4.5 nm, showing a single peak distribution, while the signal in the micropore region is relatively weak.
[0121] DZ-4 exhibits a unimodal mesoporous distribution at 5.2 nm, without microporous characteristics.
[0122] This indicates that the gradient gelation method of the present invention achieves multi-level precise control of the mesoporous structure by precisely controlling the degree of gelation and gelation rate of aluminum sol, forming a through-type multi-level porous system that is more conducive to mass transfer.
[0123] Long-term stability comparison
[0124] CZ-1 and DZ-1 were treated in an air atmosphere containing 10 vol% water vapor at 650℃ for 4 h, 8 h, 16 h, and 24 h, respectively, and the changes in specific surface area were measured.
[0125]
[0126] After 24 hours of harsh hydrothermal treatment, CZ-1 still retained 75% of its specific surface area, while DZ-1's surface area decreased significantly to 35%. This fully demonstrates that the gradient interface coupling structure endows the composite carrier with excellent hydrothermal stability, which has significant advantages in long-term operation of industrial plants.
[0127] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A molecular sieve and γ-alumina blended composite carrier, characterized in that, The composite carrier has a gradient interface coupling structure and includes: A hierarchical pore structure having interconnected micropores, mesopores and macropores, wherein the micropores have a diameter of 0.4 to 1.2 nm, the mesopores have a diameter of 3 to 15 nm, and the macropores have a diameter of 50 to 500 nm. A gradient interface coupling layer is located between molecular sieve particles and γ-alumina matrix, with a thickness of 2 to 20 nm, wherein the silicon-alumina atomic ratio decreases in a gradient from the molecular sieve side to the alumina side, and contains Si-O-Al chemical bonds. Based on the total mass of the composite carrier, the mass percentage of molecular sieve is 15%–65%, and the mass percentage of γ-alumina is 35%–85%. Specific surface area is 280–550 m² 2 / g, total pore volume is 0.40~0.85 cm³ 3 / g, with a crushing strength of 80~200 N / cm, and a specific surface area retention rate of ≥85% after hydrothermal treatment at 650℃ for 4 h.
2. The composite carrier according to claim 1, characterized in that, Based on the total mass of the composite carrier, the mass percentage of molecular sieve is 30%–50%, and the mass percentage of γ-alumina is 50%–70%.
3. A method for preparing a molecular sieve and γ-alumina blended composite support, characterized in that, Includes the following steps: Step (1): Mix molecular sieve raw powder with silane coupling agent in organic solvent, react at 50-78℃ for 2-8 h, and after post-treatment, obtain surface functionalized molecular sieve; Step (2): Disperse the surface-functionalized molecular sieve in water to obtain suspension A; mix boehmite with water and acid and perform sol-gel to obtain aluminum sol B; mix suspension A and aluminum sol B, and then add alkali to adjust the pH to 6.0-8.0 to gel the aluminum sol. After aging, obtain a molecular sieve-aluminum gel composite with a gradient interface layer. Step (3): The molecular sieve-aluminum gel composite is mixed with molding aid and water, kneaded, extruded and shaped, dried and then calcined at 450-650℃ to obtain the composite carrier.
4. The preparation method according to claim 3, characterized in that, In step (1), the silane coupling agent is selected from at least one of γ-aminopropyltriethoxysilane, propyltrimethoxysilane or γ-methacryloxypropyltrimethoxysilane, and its amount is 0.5% to 5% of the molecular sieve raw powder mass. The organic solvent is anhydrous ethanol.
5. The preparation method according to claim 3, characterized in that, In step (2), the solid content of the suspension A is 5% to 25%; the temperature of the sol is 60 to 90°C, the time is 1 to 4 h, the acid used is nitric acid, and the pH value of the sol system is 3.5 to 5.0; in the aluminosilicate B, the mass ratio of boehmite to water is 1:3 to 1:
10.
6. The preparation method according to claim 3, characterized in that, In step (2), suspension A is added dropwise to aluminum sol B at a dropping rate of 1 to 10 mL / min, and the stirring speed during the dropping process is 200 to 800 r / min. After the dropping is completed, stirring continues for 0.5 to 2 h. The alkaline solution is ammonia water, and its dropping rate is 0.5 to 2.0 mL / min. The aging treatment time is 2 to 8 h.
7. The preparation method according to claim 3, characterized in that, In step (3), the molding aid is selected from at least one of guar gum powder, carboxymethyl cellulose or polyethylene glycol, and its dosage is 1% to 5% of the total mass of the molecular sieve-aluminum gel composite; the drying is carried out at 80 to 120°C for 4 to 12 h; the calcination heating rate is 1 to 5°C / min, and the calcination time is 3 to 8 h.
8. The preparation method according to claim 4, characterized in that, In step (1), the silane coupling agent is propyltrimethoxysilane, and its amount is 2% of the mass of the molecular sieve powder.
9. The preparation method according to claim 5, characterized in that, In step (2), the solid content of suspension A is 15%; the temperature of the gelation is 75°C and the pH of the gelation system is 4.0; the alkaline solution is ammonia water, and the final pH value is adjusted to 7.0; the aging treatment time is 4 h.